Analisis Besaran Biaya Obat Beberapa Penyakit Rawat Jalan dan Faktor- Faktor yang Mempengaruhi di Rs. Awal Bros Bekasi Tahun 2014 - Hadiningsih, Hastuti (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
The background of this study is the high bill outpatient drug costs when compared with the costs borne by BPJS by embracing INA CBG's tariff system. So, we need a more in-depth analysis of the factors that affect the amount of health care costs. This study uses a cross-sectional study with quantitative methods, by looking at factors of age, sex, prescription drugs, doctor and health insurance status in accordance with the secondary data obtained through medical records and bills medicine outpatient services. And based on the results of the study, factors that affect the cost of the drug is age, the guarantor, the number of drug items (R /) and the use of generic drugs. So as to address these issues need for clinical previllage for outpatient cases and policies that govern rational prescribing.